Ekplorasi mendalam: Tradisi Tabot dalam kearifan lokal Bengkulu - Andika, Andika (Maliki Interdisciplinary Journal, 2024)
This article aims to provide an in-depth understanding of the tabot tradition in Bengkulu's local wisdom. Starting from an introduction explaining the relevance of this tradition in Bengkulu culture to a discussion of history, the meaning of important elements, and its social impact. This article uses the library research method by collecting and processing data from various literary sources, both journals and books. This research tends more towards descriptive research, which in this study describes the existence of the Tabot tradition and the results of data obtained from various sources to be presented as written work. The research results show that the Tabot Ceremony in Bengkulu is a tradition passed down from generation to generation which is carried out every year and is used as a regional asset. The tabot ceremony is carried out with several rituals, each ritual contains a meaning and message and tells a history or story.